Impact of Climate Change on Water Availability: Systematic Literature Review - Nasrul, Nasrul; Amdah, Misdar; Maru, Rosmini (PT. Pubsains Nur Cendekia, 2024)
Climate change has caused shifts in the distribution of rainfall and drought. This research aims to analyze the impact of climate change on water availability based on several research results that have been carried out. This research uses the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) method along with VosViewer for bibliometric analysis. Data sourced from Publish or Perish and Google Scholar in 2015–2024 totaling 500 journals. Data was reduced using inclusion and exclusion criteria so that 40 journals were obtained to be reviewed and 10 journals with the highest citations to be discussed. Climate change has a significant impact on the availability of air on Earth. Rising earth temperatures can cause river water to become less abundant and air quality to become worse, which in turn can affect human life and biota that depend on the air. This research will have implications for efforts to deal with climate change as part of the influence on the availability of clean water.